PERSEPSI SOSIAL MASYARAKAT TERHADAP ADIAN NAPITUPULU SEBAGAI ANGGOTA LEGISLATIF WILAYAH DAERAH PEMILIHAN IV KABUPATEN BOGOR - Maulana , Rizki; Yusnita , Titien; Ernawati , Erna (Fakultas Ilmu Dakwah dan Komunikasi, 2024)
This research aims to determine the Sundanese community's perception of a leader who is an immigrant and not a native of the Sundanese tribe. This research method uses qualitative. Case study approach. This research involved informants from the Bogor Regency community who live in Electoral District IV Bogor Regency and consisted of aid recipients, Adian Napitupulu's success team, religious leaders and community leaders. The results of this research are that the people in electoral district IV Bogor Regency have a positive view of Adian Napitupulu's performance as a member of the Legislature. Adian Napitupulu has effectively represented the interests of the community in parliament. Adian Napitupulu has been active in fighting for policies that are beneficial for the electoral district IV of Bogor Regency, both related to infrastructure and other social issues. Positive perceptions related to integrity, commitment and honesty